Takhrij and Syarah Hadith of Agrotechnology: Content and Benefits of Black Seed - Silvi Nur Azmi; Wahyudin Darmalaksana; Liberty Chaidir (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the Black Seed. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research are the content and benefits of Black Seed, a medicine for various diseases that is recommended by the Prophet Muhammad. The conclusion of this study is the takhrij and syarah hadith of the Prophet SAW about the content and benefits of Black Seed starting from reducing pain, anti-inflammation, and shortness of breath.